Clinical and CBCT assessment of crestal bone changes in immediate and delayed placement of implant - Randhir Kumar; Smita R Priyadarshini; Shreyas Surendra Gotoorkar; Ruhi Sidhu; Faris Jaser Almutairi; Baburajan Kandasamy; Vardarajula Venkata Ramaiah (Wolters Kluwer Medknow Publications, 2023)
Objectives: The present research was done to assess the crestal bone changes in immediate and delayed dental implant placement. Materials and Method: Twenty four implant sites in participants within the age group of 25-60 years in both genders were done with immediate (Group I) and delayed implant (Group II) placement method. Clinical parameters such as pain, mobility, and radiographic assessment for crestal bone alterations were recorded at baseline, 3 months, and 6 months. Results and Conclusion: On intergroup assessment, the mean variation of the pain, mobility, and crestal bone loss was insignificant.